Manajemen Kompensasi Pendidik Pendidikan Anak Usia Dini : Studi di Kelompok Bermain Azzaqiatul Iman - Nawangsih, Nawangsih; Sopiah, Siti Aes; Hidayat, Ara (Universitas Islam Negeri Raden Intan Lampung, 2020)
This study aims to describe efforts to increase teacher compensation in Kober Azzaqiatul Iman Garut. This study used descriptive qualitative method. The method of data collection is through observation, interviews and documentation, with speakers of principals, teachers, and guardians of students and researchers as key instruments. The results showed the fact that the management of Educator compensation by Kober Azzaqiatul Iman was carried out through several stages, namely: (1) internal party coordination through routine meetings, daily, weekly, monthly, semesterly or annually, usually done as an emotional reinforcement and mutual trust between heads and educator. (2) external coordination, that are parent meetings four times a year, advocating, participating in village discussion, actively participating in PAUD, HIMPAUDI, and strengthening activities to the relevant education offices.